Approaches in addressing family issues in Muslim world: a critical appraisal - Boukerroucha, Halima; Asmaa, Akli (2017)
This research is an attempt to critically appraise the family issues in legislation, educational plans, and religious guidance to assess the extent of the fractional fiqhi approach and political and ideological considerations in addressing family issues. The research employs a critical analytical methodology where approaches and views are critically analysed. The study then applies a comparative study where different views are examined and conflicting evidence are compared. The research will be qualitative where the data will be collected from classical treatises of Muslim scholars, local and international statutes and documents on Family issues as well as contemporary works. The research will study the concept of family from Shariah perspective and examine the main approaches in addressing family matters that have influenced the position of the family in the Muslim world. It then provides some prospects and suggestions for a better approach to family issues. The objective is to propose a platform for a better putting in place a methodological framework based on the principles and objectives of Shariah to ensure family issues are addressed from a holistic that combines between religious requirements and reality necessities, this is to ensure comprehensive care for family matters that covers religious requirements and contemporary needs.